Assessing the Effectiveness of Different Modes of Diclofenac in Post-Endodontic Pain Management: A Randomized Controlled Clinical Study. (Bangladesh Journal of Medical Science, 2025)
Background The main factor for most people to routinely seek endodontic therapy is pain. However, the pain may still be reported after the endodontic therapy. Thus, the use of pre-operative analgesics has been shown to reduce the onset of postoperative pain. The study was planned to assess the effectiveness of pretreatment with diclofenac in managing postendodontic pain while comparing the efficacy of two modes of delivery systems i.e. oral, and transdermal patches. Material and methodology A randomized controlled trial was done on 180 adult subjects with irreversible pulpitis. The patients were aggregated into three groups: Oral (group B) and transdermal (group C) administration of diclofenac was done in patients just before undergoing any endodontic treatment. While in (group A) acetaminophen, a rescue pill was administered to the patients. The pain was gauged using “Visual Analog Scale (VAS)” and the pain frequency was measured at 8, 12, 24, 48 and 72 hours after the endodontic treatment in all three groups that were analysed statistically. Results VAS was greater for the oral Diclofenac groups than the control group. On inter-group comparison between the groups control and the oral Diclofenac, it was seen that there was no significant variation at the end of 8, 12, 24, 48 and 72 hrs. At 8 hours, there was a significant variance between the groups transdermal patch and the oral Diclofenac [p=.036], with a greater change in the VAS in transdermal patch than in the oral diclofenac group. On inter-group comparison between the Control group and the Transdermal Patch, There was a significant variance between the two groups at 12, 24, 48, 72 hours, with p=.040, p=.009, p=.001 and p=.002 respectively. Conclusion A promising analgesic technique for the treatment of endodontic pain appears to be the transdermal diclofenac patch. The study places a strong emphasis on using preoperative analgesics to lessen postendodontic pain.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 440-449